Making sense of professional enablers’ involvement in laundering organized crime proceeds and of their regulation - Levi, Michael (Trends in organized crime, 2021)
Money laundering has ascended the enforcement and criminological agenda in the course of this century, and has been accompanied by an increased focus on legal professionals as ‘enablers’ of crime. This article explores the dynamics of this enforcement, media and political agenda, and how the legal profession has responded in the UK and elsewhere, within the context of ignoring the difficulties of judging the effectiveness of anti money laundering. It concludes that legal responses are a function of their lobbying power, the determination of governments to clamp down on the toxic impacts of legal structures, and different legal cultures. However, it remains unclear what the effects on the levels and organization of serious crimes for gain are of controls on the professions.